Solid-Phase Extraction and Spectrophotometric Determination of Mercury with 6-Mercaptopurine in Tobacco and Tobacco Additive - ZHOU, YUANQING; WU, ZHAOLU; ZHAO, XUEBING; FU, DENGGAO (Asian Journal of Chemistry, 2010)
A new method for the determination of trace amounts of mercury based on the reaction of Hg(II) with 6-mercaptopurine (6-MP) and the solid phase extraction of the complex on C18 membrane disks was developed. The 6-MP selectively reacts with Hg(II) to form a complex in the pH range of 5-8. This complex was preconcentrated by solid phase extraction with C18 disks. An enrichment factor of 50 was achieved. The molar absorptivity of the complex is 4.17 × 104 L mol-1 cm-1 measured at 315 nm. The Beer’s law is obeyed in the concentration range of 0.05-5.4 μg mL-1. The relative standard deviation for eleven-replicated measurement of 0.024 μg mL-1 is 1.5 %. The detection limit is 0.4 μg L-1 in the original samples. The advantage of the method is that the determination of Hg(II) is free from interference of the almost all cations and anions found in samples. The determination of Hg(II) in tobacco and tobacco additive was carried out by the present method and cold vapour atomic absorption spectrometry (CVAAS). The obtained results by the present procedure were in good agreement with those of the CVAAS, so that the applicability of the proposed method was confirmed to the real samples.